The Psychometric Properties of a Short UPPS-P Impulsive Behavior Scale Among Psychiatric Patients Evaluated in an Emergency Setting - Dugré, Jules Roger; Giguére, Charles-Édouard; Percie du Sert, Olivier; Potvin, Stephane; Dumais, Alexandre; , Consortium Signature (Frontiers in Psychiatry, 2019)
Objective: Impulsivity is a multidimensional construct that has an important role for the understanding of diverse psychopathologies and problematic behaviors. The UPPS-P impulsive behavior scale, measuring five distinct facets of impulsivity, has been subject to several studies. No study has investigated the clinical utility of this questionnaire amongst an unstable psychiatric population. The aim of the current study is to examine the psychometric properties of the short version of this scale in a psychiatric emergency unit. Method: The S-UPPS-P was administered to 1097 psychiatric patients in an emergency setting, where a subgroup of 148 participants completed a follow-up. The internal consistency, the construct validity, the test-retest reliability and the convergent validity of the scale were examined. Results: Confirmatory factor analyses supported a five-factor solution. Results indicated good psychometric properties across psychiatric diagnoses and gender. The S-UPPS-P was partially invariant across sexes. The authors have found differences on the loading of one item and on the thresholds of two items from lack of premeditation and positive urgency subscales. Conclusion: This validation study showed that the UPPS-P conserved good psychometric properties in an unstable psychiatric sample, indicating that the instrument can be utilized in such settings.